Disability in Adult Patients with Chronic Low Back Pain in a North Central Nigerian Hospital - Kortor, Namgwa Joseph; Iyor, Fidelis T.; Yongu, William T.; Elachi, Itodo C.; Mue, Daniel D. (Nigerian Journal of Orthopaedics and Trauma, 2018)
Background: Chronic low back pain (CLBP) is a common health problem that is often associated with physical disability and reduced quality of life. Functional disability is the inability to perform age‑approximate physical, mental and social activities of daily living. It is, therefore, pertinent to determine the prevalence of disability in patients with CLBP as this will help clinicians to look out for risk factors associated with disability and thus facilitate management decisions. Aim: The aim of this study is to determine the prevalence and level of disability in patients with CLBP. Patients and Methods: Patients with CLBP observed at the orthopaedic clinic of Benue State University Teaching Hospital, Makurdi from June 2016 to February 2017 were recruited for this study. A designed questionnaire was used to collect data. Oswestry low back pain disability questionnaire was used to assess the level of disability. Results: A total of 126 patients with CLBP were evaluated, consisting of 45 males (35.7%) and 81 females (64.3%) with a male:female ratio of 1:1.8. The prevalence of disability in patients with CLBP in this study was 78.6%. 66 (52.4%) of patients had a moderate disability, 32 (25.4%) of patients had a severe disability, 27 (21.4%) of patients had mild or no disability and only one patient (0.8%) was crippled. There was a significant association between the age and level of disability (P = 0.001). Conclusion: Disability in patients with chronic back pain is a common health problem in our environment. Determination of disability prevalence will create more awareness for the need to assess risk factors and evaluate the effectiveness of various treatment options.